2008
DOI: 10.1126/science.1155832
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Neotropical Diversity: Greater Than the Sum of Its Parts

Abstract: The diversity of tropical herbivorous insects has been explained as a direct function of plant species diversity. Testing that explanation, we reared 2857 flies from flowers and seeds of 24 species of plants from 34 neotropical sites. Samples yielded 52 morphologically similar species of flies and documented highly conserved patterns of specificity to host taxa and host parts. Widespread species of plants can support 13 species of flies. Within single populations of plants, we typically found one or more fly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(108 citation statements)
references
References 26 publications
5
103
0
Order By: Relevance
“…The observation that taxon range size explains a significant proportion of between taxon variance in diversity of gall-inducing midges accords well with previous studies showing that plant taxon range size is an important predictor of phytophagous insect diversity in the Palearctic [9,17] and Neotropics [11]. Plant taxa with larger ranges (and higher abundances within those ranges) come into contact with a greater diversity of other plant species and their insect fauna and thus may present larger colonization targets relative to plant taxa with smaller geographical extent [38].…”
Section: Discussionsupporting
confidence: 90%
“…The observation that taxon range size explains a significant proportion of between taxon variance in diversity of gall-inducing midges accords well with previous studies showing that plant taxon range size is an important predictor of phytophagous insect diversity in the Palearctic [9,17] and Neotropics [11]. Plant taxa with larger ranges (and higher abundances within those ranges) come into contact with a greater diversity of other plant species and their insect fauna and thus may present larger colonization targets relative to plant taxa with smaller geographical extent [38].…”
Section: Discussionsupporting
confidence: 90%
“…For example, Nyman et al [12] found that nearly half of recent speciation events in nematine sawflies do not involve niche shifts, undermining the common, ecologybased explanation of herbivorous insect diversification. Similarly, Condon et al [13] showed that Blepharoneura fruitflies, when sampled across South America, exhibit much higher diversity than would be expected from the sum of available niches (host plant diversity and plant parts), suggesting that non-ecological, geographical processes have contributed significantly to the evolution of their diversity. Therefore, allopatric, non-ecological modes of speciation, as found in Micropterigidae, is probably an important mechanism generating herbivorous insect diversity, but is commonly overlooked because the geographical scale at which it operates differs greatly depending on the dispersal ability of the insect.…”
Section: Resultsmentioning
confidence: 98%
“…1), and often, additional morphological qualitative character states could be used to identify these species. Inasmuch as time and resources for alpha-taxonomy are limited, a DNA-barcoding first pass through an unknown or understudied taxa or geography will aid species discovery, subsequent identification of specimens, and strategies for subsequent alpha-taxonomy (16,17,19).…”
Section: Discussionmentioning
confidence: 99%